Moral Reasoning dan Skeptisisme Profesional Memoderasi Pengaruh Independensi Terhadap Kualitas Audit - Rahayuningsih, Endang Retno; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 29 No 3 (2019)DO - 10.24843/EJA.2019.v29.i03.p05, 2019)
The purpose of this study is to determine the ability of moral reasoning and professional skepticism to moderate the influence of independence on audit quality at PT. Bank Sinar Mas MSIG Bali Province. This research was conducted in eight offices of PT. Bank Sinar Mas MSIG found in the Bali Region by using 40 internal auditors as a sample using the census method. Data collection is done by distributing questionnaires and tested through the Moderated Regression Analysis (MRA) technique. Based on the results of the analysis, the independence variable has a positive effect on audit quality. Moral reasoning strengthens the effect of independence on audit quality. Professional skepticism reinforces the influence of independence on audit quality. Keywords : Independence; Moral Reasoning; Professional Skepticism; Audit Quality.